The efficacy of sodium chloride application in the control of fish lice (Argulus sp) infection on tilapia (Oreochromis niloticus) - Dewi, Rita Rosmala; Siallagan, Wordianti; Suryanto, Dwi (Acta Aquatica: Aquatic Sciences Journal, 2018)
The Argulus sp infection in freshwater fish including tilapia (Oreochromis niloticus) causes the serious problem in aquaculture. Despite the scarce of the preventive action in parasite infection, the application of salt mostly have been done in fish farming to overcome these parasites. The sodium chloride (NaCl) was used in farm because it was safe for water environment as well as it was inherent therein. The effectiveness of sodium chloride to control ectoparasites Argulus sp in tilapia juvenile was tested in laboratory. The fishes were infected by Argulus sp. and they are treated short term dip with three doses of sodium chloride namely 3 ppm, 6 ppm and 9 ppm for ten days. The  prevalence of parasites, the parasites intensity, and survival rate were examined and the results  were evaluated using statistic. The result showed that the NaCl salt application significantly affected the prevalence, the parasite intensity and the survival rate of fishes. The best dose that give the lowest prevalence, the lowest parasite intensity and the highest survival rate was the G3 (9 ppm dose).